The Effect of Opinion Readability on the Impact of U.S. Supreme Court Precedents in State High Courts. (24th November 2019) - Fix, Michael P.; Fairbanks, Bailey R.
Abstract : Objective: This article examines whether more readable U.S. Supreme Court opinions are cited with greater frequency in state courts of last resort. Methods: We use random slope, random intercept multilevel models to analyze 30 years of state high court citations to U.S. Supreme Court majority opinions issued during the 1987–2006 terms. Results: Our analysis reveals that opinion readability exerts a strong substantive impact on citation rates. This effect holds while accounting for a variety of factors previously shown to influence citation rates. Conclusion: Institutional constraints, workload considerations, and audience costs should lead state high courts to find clearly written opinions more attractive than jargon‐laden ones. This makes the readability of a U.S. Supreme Court precedent a useful heuristic for state courts when selecting among potential relevant precedents. As these courts play a major role in implementing U.S Supreme Court decisions, our findings indicate that the readability of U.S. Supreme Court opinions has a strong effect on their long‐term impact.